Perencanaan Ulang Tebal Perkerasan Lentur Berdasarkan Faktor Kerusakan Jalan (Studi Kasus Ruas Jalan Selebar-Sebakul Kota Bengkulu) - Elly Tri Pujiastuti; Ahmad Rifani (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2019)
Abstract A road is one of the infrastructures for the community to reach an area to another region. In this case to facilitate economic relations activities, both between one city and another city, between cities and villages, between villages and other villages. At present time the construction planning or the thickness of road construction can be done in many ways (methods), among others: ASSTH (American Association Of State Highway And Transportation Officials) and United States (The Asphalt Institute), Rote Note ( England), AUSTROADS (Australia), and Bina Marga (Indonesia). Analyzing the factors of the damage, calculation planning Flextual Pavement Thickness with Component Analysis Method from Bina Marga, 1987. Analyzing of the cuases of damage will increase the accuracy of the research results. Based on the survey of the road conditions, the damages that occurred are fine cracks, alligator cracks, edge cracks, cracks, joint reflec cracks and pavement, rutting, peels, potholes, shoving and weathering. The most dominant damages type that happend is pothole crack. The method used is California Bearing Ratio (CBR), and to determine the thickness by using the field analysis of average daily traffic. Based on the result of the analysis and the counting that have been conducted using Bina Marga method, the average of CBR is 6,6%, the number of the Capacity of Soils is 5,2 %. The thickness of the flexible pavement layer that is required to enhance the section of Jalan Selebar – Sebakul, Kota Bengkulu the based on the component analysis method of SKBI (Indonesia Building Construction Standards) 1987, is 55 cm with the details from the 6732 vehicles of average daily traffic. The calculated results, it is obtained that each pavement layer thickness is the surface course Laston MS 744 kg with a thickness of 10 cm. The base course is using grade A split with the thickness of 20 cm. The subbase course is Grade A sand and stone aggregates with 25 cm thickness.